Development of an IoT-Enabled Automatic Poultry Feeder and Cage Temperature Monitoring System Using Microcontroller Technology - Setiadi, Teguh; Arifiandi, Tody Inggil (Universitas Pendidikan Nasional, 2024)
In general, chicken farmers still use conventional systems to feed the chickens they raise. They use their hands to sprinkle feed on the feed poles and walk along the cage where the cages for the chickens they raise are very large. Such activities for chicken farmers will take up time and energy. Feeding chickens can be made easier by using mechanical devices controlled by electronic equipment. The aim of this research is to design and create an IoT-based automatic chicken feeding tool. In designing this tool, we started by designing an IoT-based automatic chicken feeding tool. Where the Servo is a feed pusher in the pipe to spill animal feed into the feeder. The results of this research show the performance of Servo which functions to provide automatic chicken feed. The results of IoT testing which functions as a timer for giving chicken feed to this tool are quite accurate. This is proven by the difference between the time on the tool and the time on the laptop of only 1 second. And temperature monitoring can be seen on the LCD, if the temperature is above 30 degrees, the fan or fun will turn on, and if it is below 30 degrees, the light will turn on automatically.